Diagnosing Fetal Aneuploidy in Australia: The Impact of Prenatal Screening and the Integration of New Technology - Maxwell, Susannah (Curtin University, 2017)
This thesis explores the historical uptake, impact, performance and outcomes of prenatal screening for fetal aneuploidy in Western Australia. New models were developed to evaluate the economic and clinical impact of new non-invasive cell free DNA (NIPT cfDNA) testing. NIPT can improve the detection of fetal Down syndrome and reduce invasive diagnostic testing and procedure related loss. These studies provide evidence to support the translation of NIPT into national public health policy.